A fascist century : essays - Griffin, Roger 1948- (Palgrave Macmillan, 2008)
'I am no longer human. I am a titan. A god!' : the fascist quest to regenerate time -- Modernity under the new order : the fascist project for managing the future -- Exploding the continuum of history : a non-Marxist's Marxist model of fascism's revolutionary dynamics -- Fatal attraction : why Nazism appealed to voters -- Hooked crosses and forking paths : the fascist dynamics of the Third Reich -- 'No racism thanks, we're British' : how right-wing populism manifests itself in contemporary Britain -- 'Europe for the Europeans' : fascist myths of the European new order 1922-1992 -- Fascism's new faces (and new facelessness) in the 'post-fascist' era -- The fascination of fascism : a concluding interview with Roger Griffin